Stages of packaging creation: from idea to store shelf - Shoponiak, Yuliia (Global Prosperity, 2025)
Abstract. The article is devoted to highlighting the main stages of creating packaging as an element of product and marketing design. The purpose of the article is to identify and systematize the main stages of creating packaging as an integrated element of product and marketing design. The work used general scientific methods: analysis, generalization, systematization and comparison. The results of the study show that the process of creating packaging includes four consecutive stages. First, the functional purpose is determined - technical, operational and protective properties of the packaging, its ergonomics and compliance with logistical requirements. Then, consumer behavior is analyzed, which affects visual and tactile solutions: packaging should be understandable, attractive and adapted to the expectations of the target audience. At the environmental stage, materials that meet the principles of sustainable development and innovative communication formats are considered. The final stage is the integration of packaging into the brand's marketing strategy, where it performs the functions of differentiation, information and support of brand identity. Special attention is paid to the practical implementation of the proposed model using the example of confectionery packaging design. It is concluded that packaging is becoming a tool for emotional interaction with the consumer, combining aesthetic appeal with functionality and environmental responsibility. The role of packaging as a strategic brand resource capable of forming sustainable loyalty, strengthening advertising messages and maintaining the integrity of visual communication is also emphasized. It is an important component in ensuring the competitiveness of the product in the market, especially in conditions of high product range saturation and growing environmental expectations from consumers.